Special Investment Support Under the Agricultural Reorganisation Programme 1995-2000 - Juhász, Lajos (Acta Agraria Debreceniensis, 2002)
Since the political changes in Hungary, agricultural businesses have worked in a declining economic environment and hectic market situation, with a widening price gap between agricultural and industrial products and low profitability. A declining export comes then by no surprise. The sector has not been able to even benefit from export opportunities provided in the European Agreement. The area least benefiting from quotas is animal products (beef, mutton, lamb, slaughtered chicken, cheese, egg). The ministry of agriculture was lagging behind in responding to these problems, and it was as late as in 1995 when it launched a reorganisation programme for export stocks fund build-up (5).The author has conducted empirical studies on agricultural enterprises in Csongrád county to see what results the special investment support delivered under the reorganisation programme produced. The fundamental aim of the reorganisation programme for export stocks fund build-up was to boost exportable Hungarian animal product stocks in a bid for businesses to better benefit from the preferential quotas set by the European Agreement. The author examined how the special investment support scheme succeeded in its aims, whether livestock grew considerably in its wake, whether farmers were able to attain exportable quality and what development funds enterprises were able to raise.